2012
DOI: 10.1890/es11-00318.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental education on sense of place among urban youth

Abstract: Abstract. Research suggests that an ecologically informed sense of place, including strong place attachment and ecological place meaning, contributes to pro-environmental behaviors. Yet it is unclear whether an intervention such as environmental education can intentionally influence sense of place, especially in cities. To investigate the impact of urban environmental education programs on sense of place, we used pre/post surveys of youth in 5-week environmental and non-environmental summer youth programs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 75 publications
1
99
0
6
Order By: Relevance
“…Kudryavtsev, Krasny, and Stedman (2012) reported that educational trips give opportunity for real first hand experiences and brings welcome change to monotonous presence of teachers. Also, available literature reviewed noted that service learning had impact on students' social development, civic responsibility, career interests and skills in solving environmental problems (Warren, 2012;Christine;Durlak & Dymnicki 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kudryavtsev, Krasny, and Stedman (2012) reported that educational trips give opportunity for real first hand experiences and brings welcome change to monotonous presence of teachers. Also, available literature reviewed noted that service learning had impact on students' social development, civic responsibility, career interests and skills in solving environmental problems (Warren, 2012;Christine;Durlak & Dymnicki 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have demonstrated that the stewarding of local urban nature also promotes a sense of place among communities (Stedman, 2003;ODPM, 2004;Kudryavtsev et al, 2012;Tidball and Stedman, 2013) which in turn builds on individual and community well-being.…”
Section: Participatory Approaches To Management Of Urban Green Commonsmentioning
confidence: 99%
“…Second, parallel to Pantzar and Shove (2010), who talk about meanings related to objects, i.e., walking sticks for the fit or for the infirm, and doing, i.e., walking for fun or for fitness, we are particularly interested in meanings related to place and practice. We draw from a significant body of work on sense of place, symbolism, and social-ecological memories in civic ecology practices (Barthel et al 2010, Kudryavtsev et al 2012, Tidball 2014. Finally, the product or material element in studies of consumption practices has focused on such things as walking sticks or electric appliances; we have replaced consumer items with the land, water, or biological resource that is the focus of stewardship activities.…”
Section: Practice Theory and Civic Ecology Practicesmentioning
confidence: 99%